Pengaruh Pemberian Ekstrak Rimpang Temulawak (Curcuma Xanthorrhiza Roxb.) dan Jintan Hitam (Nigella Sativa) terhadap Profil Lipid Tikus Sprague Dawley Dislipidemia - Budiarto, Andika Agus; Wibowo, Alem Pramudita; Putri, Stella Andriana; Shabrina, Nadine Nurani; Ngestiningsih, Dwi; Tjahjono, Kusmiyati (Faculty of Medicine, Universitas Padjadjaran, 2017)
Terapi jangka panjang dislipidemia dengan simvastatin dapat menimbulkan berbagai efek samping sehingga perlu alternatif terapi, salah satunya dengan temulawak dan jintan hitam. Kandungan curcumin pada temulawak dan thymoquinon pada jintan hitam diperkirakan dapat memperbaiki profil lipid pasien dislipidemia. Tujuan dari penelitain adalah membuktikan efek pemberian ekstrak temulawak dan ekstrak jintan hitam terhadap profil lipid tikus Sprague dawley dislipidemia. Penelitian menggunakan true experimental design dengan post test randomized controlled group design. Penelitian ini dilakukan di Laboratorium Penelitian dan Pengujian Terpadu (LPPT)–Layanan Pra Klinik Pengembangan Hewan Percobaan (LP3HP) Universitas Gajah Mada Yogyakarta dan di Laboratorium Biologi Fakultas Sains dan Matematika Universitas Negeri Semarang periode 18 Februari–8 Maret 2016. Sebanyak 42 ekor tikus Sprague dawley dibagi menjadi 6 kelompok, yaitu kelompok K1 (kontrol normal), kelompok K2 (kontrol dislipidemia), kelompok P1 (200 mg/kgBB ekstrak temulawak), kelompok P2 (400 mg/kgBB ekstrak jintan hitam), kelompok P3 (0,18 mg/200 gramBB simvastatin), dan kelompok P4 (200 mg/kgBB ekstrak temulawak dan 400 mg/kgBB ekstrak jintan hitam). Kadar kolesterol LDL, HDL dan kolesterol total diukur dengan CHOD-PAP. Hasil penelitian menunjukkan kelompok K2 memiliki kadar tertinggi kolesterol total (69,1 ± 2,41) dan LDL (25,9 ± 2,16), serta memiliki kadar terendah HDL (30,68 ± 5,25). Uji ANOVA pada kolesterol total dan LDL menunjukan perbedaan bermakna (p<0,05), sedangkan pada HDL tidak bermakna (p>0,05). Disimpulkan, ekstrak temulawak dan ekstrak jintan hitam berpotensi menurunkan kadar LDL dan kolesterol total, serta menaikkan kadar HDL pada tikus Sprague Dawley dislipidemia. [MKB. 2016;49(1):8–14]Kata kunci: Jintan hitam, profil lipid, temulawak Effects of Temulawak (Curcuma xanthorrhiza Roxb.) and Black Cumin (Nigella sativa) Extracts on Lipid Profile: A Study on Dyslipidemic Sprague Dawley Rats The use of Simvastatin for a long term therapy of dyslipidemia can cause unwanted side effects; therefore, alternative therapies are needed, including therapy using temulawak and black cumin extracts. Curcumin in temulawak and thymoquinon in black cumin could modify the lipid profile of patients with dyslipidemia. The aim of study was to determine the effect of temulawak and black cumin extracts on serum lipid profile of dyslipidemic Sprague dawley rats. This research was conducted at Integrated Research and Testing Laboratory (PPT) -Profit Clinical Trials (LP3HP) Gadjah Mada University Yogyakarta and in Biology Laboratory Faculty of Science and Mathematics State University of Semarang period 18 February-8 March 2016. This study used true experimental design with post-test randomized controlled group design. Forty two Sprague dawley rats were divided into 6 groups: K1 for normal control, K2 for dyslipidemic control, P1 received 200mg/kgBW Temulawak extract, P2 received 400mg/kgBW black cumin extract, P3 received 0.18mg/200grBW simvastatin, and P4 received a combination of 200mg/kgBW Temulawak extract and 400mg/kgBW black cumin extract. LDL, HDL, and total cholesterol levels were determined by CHOD-PAP. The results of this study showed that K2 group had the highest level of total cholesterol (69.1 ± 2.41) and LDL (25.9 ± 2.16) but the lowest level of HDL(30.68 ± 5.25) when compared to the other groups. ANOVA analysis of total cholesterol and LDL showed a significant difference (p<0.05), while the sama analysis on HDL showed a non-significant difference (p>0.05). From the results, it is concluded that temulawak extract and black cumin extract can potentially decrease the level of LDL and total cholesterol as well as increasing the level of HDL in dyslipidemic Sprague Dawley rats. [MKB. 2016;49(1):8–14]Key words: Black cumin, lipid profile, temulawak